KEMERDEKAAN MENYAMPAIKAN PENDAPAT DIMUKA UMUM SEBAGAI MAKAR MENURUT KUHP - Fanny Fauzie (Alhurriyah, 2019)
KUHP (Penal Code Of Indonesia) is a positive Indonesian criminal law regulation which in its history, came from the Wetboek van Strafrecht voor Nederlandsch Indie (WvSNI) which contains about the crimes against the security of the state as regulated in the sub first chapter of the KUHP itself. Van Toelichting’s Memorie mentioned that treason is a translation of the Aanslag, which, if paired into English, can be interpreted as an attempt or attack. According to 87th Article of the Criminal Code, if treason has commenced according to Article 53th of the Criminal Code (Trial), on the other hand, there is a The1945 Constitution which is a Grundnorm that guarantees the freedom to express opinions that publicly as in 28th E Article, 3rd paragraph. And also, regulated explicitly in 39th Law Number, the year 1999 about expressing opinions in public, so if referring to treason as an experiment as Article 53 of the Criminal Code, it would prevent anyone from criticizing by communicating and issuing opinions. If the notice was addressed to the government by saying the current government is not good and must be replaced, the presence of the 87th Article about the Criminal Code certainly experiments intention. And the crimes against state security are also referred to as political offenses, to determine the suspects in this political offense, an in-depth study must be carried out, so this is the reason why the writing is carried out. The typology of the research used is the normative juridical (doctrinal) library method. So in this study, we can see whether it is appropriate if the criminal offense of this treason can be applied as the 87th Article about Criminal Code without interpreting the betrayal as an aanslag or attempt or an attack connected to the existence of Guarantees in Delivering Opinions.